Comparison of anesthetic efficacy of intrathecal 1% isobaric 2-chloroprocaine with 0.5% isobaric ropivacaine for inguinal hernia surgeries - Suman Prabha Tirkey; Suman Gupta; Abhishek Gupta; Kapil Ahirwar; Preeti Goyal (Asian Journal of Medical Sciences, 2023)
Background: Inguinal hernia repair is one of the most common surgical conditions. In the absence of other comorbidities, it can be performed as a day-care procedure. Spinal anesthesia is most preferred technique this surgery. Local anesthetics having rapid and smooth onset of action, good intraoperative analgesia, short recovery period, and least side effects are preferred. Aims and Objectives: The objective of the study was to compare the anesthetic efficacy of intrathecal 1% isobaric 2-chloroprocaine (CP) and 0.5% isobaric ropivacaine for inguinal hernia surgeries. Materials and Methods: Sixty patients with ASA grade I/II scheduled for elective inguinal hernia surgeries were randomly allocated into group C (n=30), received 3 mL of 1% isobaric 2- CP and group R (n=30), received 3 mL of 0.5% isobaric ropivacaine intrathecally. Results: Demographic profile, mean time for onset of sensory blockade at T10, highest level of sensory blockade, and maximum motor blockade were comparable among the groups (P>0.05). The highest level of sensory blockade in group C is T7 and group R is T8. The mean time to two segment regression, complete sensory regression, complete motor recovery, recovery of parameters for achieving discharge criteria such as time to unassisted ambulation, drink water, micturition, and first rescue analgesia were significantly shorter in group C (P<0.0001). Visual analog scale score at the time of first rescue analgesia was significantly higher in group C (P<0.0001). Intraoperative hemodynamic changes and perioperative side effects were comparable (P>0.05). Conclusion: CP provides faster block resolution, earlier hospital discharge, and early ambulation with minimal side effects, making it a better alternative to ropivacaine for inguinal hernia surgeries.